2015
DOI: 10.1007/s00018-015-1933-z
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional actin transport is influenced by microtubule and actin stability

Abstract: Local and long-distance transport of cytoskeletal proteins is vital to neuronal maintenance and growth. Though recent progress has provided insight into the movement of microtubules and neurofilaments, mechanisms underlying the movement of actin remain elusive, in large part due to rapid transitions between its filament states and its diverse cellular localization and function. In this work, we integrated live imaging of rat sensory neurons, image processing, multiple regression analysis, and mathematical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
(101 reference statements)
1
3
0
1
Order By: Relevance
“…Actin patches consist of localized highly dynamic domains of actin filaments with general organization similar to lamellipodial structures (Spillane et al, 2011). Live imaging of chicken sensory neurons transfected with eYFP-actin, revealed that actin patches form spontaneously and are transient (Loudon et al, 2006; Ketschek and Gallo, 2010; Spillane et al, 2011, 2012, 2013; Sainath et al, 2016), and similar structures have been reported in other neuronal systems in vitro and in vivo (Korobova and Svitkina, 2008; Mingorance-Le Meur and O’Connor, 2009; Andersen et al, 2011; Spillane et al, 2011; Chia et al, 2014; Chetta et al, 2015; Hand et al, 2015). Actin patches serving as precursors to the formation of axonal filopodia and branches have also been imaged in vivo (Andersen et al, 2011; Spillane et al, 2011; Hand et al, 2015).…”
Section: Cytoskeletal Dynamics and Reorganization Underlying The Earlsupporting
confidence: 58%
“…Actin patches consist of localized highly dynamic domains of actin filaments with general organization similar to lamellipodial structures (Spillane et al, 2011). Live imaging of chicken sensory neurons transfected with eYFP-actin, revealed that actin patches form spontaneously and are transient (Loudon et al, 2006; Ketschek and Gallo, 2010; Spillane et al, 2011, 2012, 2013; Sainath et al, 2016), and similar structures have been reported in other neuronal systems in vitro and in vivo (Korobova and Svitkina, 2008; Mingorance-Le Meur and O’Connor, 2009; Andersen et al, 2011; Spillane et al, 2011; Chia et al, 2014; Chetta et al, 2015; Hand et al, 2015). Actin patches serving as precursors to the formation of axonal filopodia and branches have also been imaged in vivo (Andersen et al, 2011; Spillane et al, 2011; Hand et al, 2015).…”
Section: Cytoskeletal Dynamics and Reorganization Underlying The Earlsupporting
confidence: 58%
“…Although the overall transport of actin in axons is well characterized, the underlying molecular mechanisms are essentially unknown. One study reported veryshortrange saltatory motion of actin densities in cultured axons 161 , but it is unclear how this bidirectional shortrange movement can lead to an overall slow, anterogradely biased transport. The actin hot spots and trails described above 148 might play a role in the axonal transport of actin; however, mecha nistic details are lacking.…”
Section: Microfluidicmentioning
confidence: 99%
“…Actin dynamics is connected to many other cellular process, and of relevance to ALS/FTD, this includes axonal transport, [64][65][66] protein quality control, [67][68][69] integrated stress responses, 70 maintenance of cellular redox conditions, 31 nucleocytoplasmic shuttling, 39 and DNA damage. 35,71 Furthermore, the actin cytoskeleton supports a vast number of fundamental processes in neurons, in regulating morphogenesis and structural plasticity, axonal/dendritic initiation, axonal growth, guidance, and branching, and dendritic spine formation and stability.…”
Section: Discussionmentioning
confidence: 99%